SKRINING BAKTERI TERMOFILIK POTENSIAL AMILOLITIK DARI SUMBER AIR PANAS WAY BELERANG KALIANDA LAMPUNG SELATAN - Sefi Desfeni Mawati; Esti Harpen; Hilma Putri Fidyandini (Journal of Aquatropica Asia, 2021)
Thermophilic bacteria that produced amylase and protease have been isolated from Way Belerang hot spring, Kalianda, South Lampung. This research aims to screen and identify thermophilic bacteria that have the potential to produce thermostable amylase and protease enzymes.The research procedures included sampling, isolation of enzyme-producing thermophilic bacteria, a series of phenotypic and biochemical tests, and molecular identification by 16s rRNA. This study used 2 treatments, namely incubation temperature 37 and 50 ºC with 3 repetitions. The results showed that the optimum temperature for growth of thermophilic bacterial isolates and thermophilic bacterial isolates producing amylase enzymes was 50ºC. The bacteria isolate that had the best amylolytic enzyme activity was Isolate A.WB.50.1 with a diameter of the inhibitory zone was 15.44 mm. Isolate A.WB.50.1 has been identified by the species Pseudomonas stutzeri.